2021
DOI: 10.17051/ilkonline.2021.01.101
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Elementary School Teachers’ Professional Practice: Teachers’ Voice

Abstract: Professional practice is a crucial factor for teachers to be able to do their profession well. Its development has to be sustainable to achieve educational quality. However, the process cannot run optimally caused by various barriers faced by the teachers in the field. The objective of this study was to explore the phenomenon of the barriers to public elementary school teachers, in developing their professional practice. In order to achieve these goals, this study used qualitative descriptive design. Data coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The quality of education will not be improved effectively and efficiently, without moral, material, and spiritual support from the community, especially parents of students (Sumarsono et al 2019;Appiah-Kubi & Amoako, 2020). Furthermore, student success in learning is strongly influenced by the relationship between parents and teachers (Riastini et al, 2021). Referring to that matter, it was found that parents were unable to fully charge the success of students' learning at school.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality of education will not be improved effectively and efficiently, without moral, material, and spiritual support from the community, especially parents of students (Sumarsono et al 2019;Appiah-Kubi & Amoako, 2020). Furthermore, student success in learning is strongly influenced by the relationship between parents and teachers (Riastini et al, 2021). Referring to that matter, it was found that parents were unable to fully charge the success of students' learning at school.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, descriptive studies require exploratory activities to explore deeper understanding and knowledge. Furthermore, descriptive studies do not aim to find new theories from the data that have been collected (Riastini, 2021). In this matter, descriptive studies are utilized to explore and find deeper knowledge of existing theories.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In rural areas, some obstacles are faced to accessing computers and laptops [24]. The available technological tools are used to support the limited learning process in cities, and conditions in villages are even worse [25].…”
Section: Discussionmentioning
confidence: 99%
“…The descriptive approach is used to examine situations based on current circumstances (Siyoto & Sodik, 2015;Williams, 2007). The descriptive approach aims to observe a phenomenon in real terms based on the data collected (Hardani et al, 2020;Riastini et al, 2021). This research was conducted in SD Negeri 3 Banjar Jawa, Buleleng Subdistrict, Buleleng Regency.…”
Section: Methodsmentioning
confidence: 99%